Task Representation, Voice Expression and Beliefs about Writing: how do they relate? - Dourado, Maura Regina (The ESPecialist, 2012)
Sociocognitive research has pointed out that the process of building a mental representation of an academic writing task differs from student to student depending on both cognitive and social factors. This study aims at examining whether two Letras undergraduates represented a writing task as inviting them to voice their own ideas about the topic. The process-tracing analysis shows that social, cognitive and affective factors influenced the students’ writing process. The results point to the need to encourage our students to develop, express and sustain their own ideas about a given theme.